La gestión y la promoción cultural en los municipios distritales de Lima - Navarro Céspedes, Víctor Jesús (2020)
The objective of this article is to analyze and reflect to what extent municipal management affects the cultural promotion of municipal cultural centers in the districts of Miraflores, San Isidro and Ate in 2017. For this, the internal organization, the capital, is analyzed. human and planning that affects municipal management in the cultural promotion of municipal cultural centers in the districts of Ate, Miraflores and San isidro. This article will seek to analyze three cultural activities in three districts of Metropolitan Lima using benchmarking to find strengths and how these would help to strengthen each one. To collect information, interviews with management positions, reports, and official documents are used. of each municipality. Finally, the article presents the results that were obtained from each municipality in three fields that would be internal organization, planning and human potential. Furthermore, these results are compared, giving reflections and respective conclusions of each field.